Therapeutic Angiogenesis by a "Dynamic Duo": Simultaneous Expression of HGF and VEGF165 by Novel Bicistronic Plasmid Restores Blood Flow in Ischemic Skeletal Muscle - Ekaterina Slobodkina; Maria Boldyreva; Maxim Karagyaur; Roman Eremichev; Natalia Alexandrushkina; Vadim Balabanyan; Zhanna Akopyan; Yelena Parfyonova; Vsevolod Tkachuk; Pavel Makarevich (MDPI AG, 2020)
Therapeutic angiogenesis is a promising strategy for relief of ischemic conditions, and gene delivery was used to stimulate blood vessels' formation and growth. We have previously shown that intramuscular injection of a mixture containing plasmids encoding vascular endothelial growth factor (VEGF)165 and hepatocyte growth factor (HGF) leads to restoration of blood flow in mouse ischemic limb, and efficacy of combined delivery was superior to each plasmid administered alone. In this work, we evaluated different approaches for co-expression of HGF and VEGF165 genes in a panel of candidate plasmid DNAs (pDNAs) with internal ribosome entry sites (IRESs), a bidirectional promoter or two independent promoters for each gene of interest. Studies in HEK293T culture showed that all plasmids provided synthesis of HGF and VEGF165 proteins and stimulated capillary formation by human umbilical vein endothelial cells (HUVEC), indicating the biological potency of expressed factors. Tests in skeletal muscle explants showed a dramatic difference and most plasmids failed to express HGF and VEGF165 in a significant quantity. However, a bicistronic plasmid with two independent promoters (cytomegalovirus (CMV) for HGF and chicken b-actin (CAG) for VEGF165) provided expression of both grow factors in skeletal muscle at an equimolar ratio. Efficacy tests of bicistronic plasmid were performed in a mouse model of hind limb ischemia. Intramuscular administration of plasmid induced significant restoration of perfusion compared to an empty vector and saline. These findings were supported by increased CD31+ capillary density in animals that received pHGF/VEGF. Overall, our study reports a first-in-class candidate gene therapy drug to deliver two pivotal angiogenic growth factors (HGF and VEGF165) with properties that provide basis for future development of treatment for an unmet medical need-peripheral artery disease and associated limb ischemia.